Answer:
x=3
Step-by-step explanation:
Simplifying
4(4x + -3) = 36
Reorder the terms:
4(-3 + 4x) = 36
(-3 * 4 + 4x * 4) = 36
(-12 + 16x) = 36
Solving
-12 + 16x = 36
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '12' to each side of the equation.
-12 + 12 + 16x = 36 + 12
Combine like terms: -12 + 12 = 0
0 + 16x = 36 + 12
16x = 36 + 12
Combine like terms: 36 + 12 = 48
16x = 48
Divide each side by '16'.
x = 3
Simplifying
x = 3
27 = 5x/2 + 8y is an equation to use to solve
Answer:
6
Step-by-step explanation:
Answer: Convenience sample.
Step-by-step explanation:
Convenience sample is also known as grab or accident or opportunity samples. It is a example of non probability sample that involves selecting of subjects because of the proximity, convenience and accessibility a researcher as to them. This type of samples are not reliable for data gathering when it involves a very large sample space, let's say a global audience.
Answer:
ill joinn
Step-by-step explanation:
thank you